2015
DOI: 10.1136/bjophthalmol-2015-306634
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic surveillance of putative new autoantigens in thyroid orbitopathy

Abstract: We found that CA1 and ADH1B could attribute target autoantigens in this autoimmune disease. The high prevalence of these autoantibodies against CA1 and ADH1B in patients with TO and GD clarifies the potential clinical role for anti-CA1 and anti-ADH1B antibodies as biomarkers for GD and TO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…NMU and LPAR5 may be the targets for thyroid cancer treatment, which are abnormally expressed in thyroid cancer tissues [36]. ADH1B [37] could be the target autoantigens in thyroid cancer and play potential clinical role. Kai-Chun et al [37] demonstrated that GNA14 involves in the regulation of the thyroid function and autoimmunity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NMU and LPAR5 may be the targets for thyroid cancer treatment, which are abnormally expressed in thyroid cancer tissues [36]. ADH1B [37] could be the target autoantigens in thyroid cancer and play potential clinical role. Kai-Chun et al [37] demonstrated that GNA14 involves in the regulation of the thyroid function and autoimmunity.…”
Section: Resultsmentioning
confidence: 99%
“…ADH1B [37] could be the target autoantigens in thyroid cancer and play potential clinical role. Kai-Chun et al [37] demonstrated that GNA14 involves in the regulation of the thyroid function and autoimmunity. ALDH1A3 [37] may be the factor of mediating cancer stemness in thyroid cancer.…”
Section: Resultsmentioning
confidence: 99%
“…However, mild eye disease, with symptoms such as grittiness, pruritis and upper eyelid retraction occurs in 25% of patients with HT [5] and TRAb levels as measured by TSI/Thyretin are negative [26], indicating the possibility of a different eye disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to be a useful biomarker for oral cancer (39). Previous study demonstrated AnxA2 participation in cell proliferation in orbital fat tissue of thyroid orbitopathy patients (45).…”
Section: Downregulation Of Anxa2 In Hepatocellular Carcinoma Cells Hamentioning
confidence: 99%